Hematopoietic Stem Cell-Derived Adipocytes Modulate Adipose Tissue Cellularity, Leptin Production and Insulin Responsiveness in Female Mice - Gavin, Kathleen M.; Sullivan, Timothy M.; Maltzahn, Joanne K.; Jackman, Matthew R.; Libby, Andrew E.; MacLean, Paul S.; Kohrt, Wendy M.; Majka, Susan M.; Klemm, Dwight J. (Frontiers in Endocrinology, 2022)
A subpopulation of adipocytes in the major adipose depots of mice is produced from hematopoietic stem cells rather than mesenchymal progenitors that are the source of conventional white and brown/beige adipocytes. To analyze the impact of hematopoietic stem cell-derived adipocytes (HSCDAs) in the adipose niche we transplanted HSCs in which expression of a diphtheria toxin gene was under the control of the adipocyte-specific adiponectin gene promoter into irradiated wild type recipients. Thus, only adipocytes produced from HSC would be ablated while conventional white and brown adipocytes produced from mesenchymal progenitor cells would be spared. Wild type mice transplanted with HSCs from mice containing a reporter gene, but not the diphtheria toxin gene, regulated by the adiponectin gene promoter served as controls. In mice in which HSCDA production was suppressed, adipocyte size declined while adipose depot weights were unchanged and the number of conventional adipocyte progenitors significantly increased. We also measured a paradoxical increase in circulating leptin levels while physical activity was significantly decreased in the HSCDA depleted mice. Finally, insulin sensitivity was significantly reduced in HSCDA depleted mice. In contrast, loss of HSCDA production had no effect on body weight, components of energy balance, or levels of several circulating adipokines and tissue-resident inflammatory cells. These data indicate that ablation of this low-abundance subpopulation of adipocytes is associated with changes in circulating leptin levels and leptin-regulated endpoints associated with adipose tissue function. How they do so remains a mystery, but our results highlight the need for additional studies to explore the role of HSCDAs in other physiologic contexts such as obesity, metabolic dysfunction or loss of sex hormone production.